(untitled) (Environment & Health, 2023)
The aim of the work was to perform a psychohygienic assessment the characteristics of the spread of emotional burnout’s features, asthenic and depressive states and aggression of students in the conditions of the use of remote (on-line) organization of educational activities. Materials and methods: The research was conducted on the basis of National Pyrohov Memorial Medical University. A complex of highly informative hygienic, medical-sociological and psychodiagnostic methods and the methods of statistical analysis was used. Results: When considering the leading characteristics of emotional burnout, first of all, it was necessary to pay attention to a significant increase in the level of expression of resistance phase indicators (р0.05), characteristic of the organization of the educational process according to the remote format. In the course of research aimed at determining the correlates of the asthenic state, it was established that under the conditions of using the remote form of education, either a decrease in the degree of their expression was observed (young women), or the indicators stabilized at the initial level (young men). When determining the characteristics of changes in the leading correlates of depression, it was noticed that under the conditions of using the remote format of the organization of the educational process, either a significant decrease in the degree of their expression was observed (young women), or the indicators stabilized at the initial level (young men) too. During the analysis of indicators of aggressive personality manifestations, it should be noted that under the conditions of remote education, statistically significant changes were observed in the characteristics of physical aggression (p